Digital Transformation Factors Affecting Vocational Students’ Learning Outcomes: Toward a Comfort-Centered Model - Abdul Rohman; Tuti Suartini (Universitas Ahmad Dahlan, 2026)
The accelerated evolution of digital technology during the Fourth Industrial Revolution has revolutionized vocational education, requiring not just technical competence but also digital and emotional adaptability. This investigation aims to develop a comfort-based model that mediates technology comfort in mediating digital preparedness, infrastructure support, technical obstacles, and learning outcomes among vocational learners. An explanatory sequential mixed-methods design was adopted, incorporating quantitative correlation studies and qualitative interviews with 59 students and 7 participants for triangulation. Quantitative findings indicated significant positive correlations between digital preparedness (r = 0.346, p < 0.05) and infrastructure support (r = 0.312, p < 0.05) with technology comfort, while technical obstacles reflected a weak and non-significant negative association (r = -0.251, ns). In addition, technology comfort significantly correlated with learning outcomes (r = 0.417, p < 0.01), substantiating its mediating function. The qualitative findings identified students' emotional experience, usability experience, and adaptive confidence as key elements of comfort. The study broadens the scope of the Extended Educational Technology Acceptance Model (EETAM) by incorporating affective processes consistent with Self-Determination Theory. This investigation identifies that promoting emotional comfort with digital support-based pedagogy can encourage students' engagement and learning ability in vocational education.